Lottery Demand and Stock Returns Preceding Earnings Announcements - Nguyen H; Truong C (John Wiley and Sons Ltd, 2025)
We document a significant positive relation between extreme positive stock returns around past earnings announcements and stock returns in the 10-day window before current earnings announcements. The average of risk-adjusted return differences between stocks with the highest earnings announcement maximum returns and stocks with the lowest earnings announcement maximum returns is 85 basis points in the 10 days leading up to earnings announcements. This is consistent with the argument that investors have a preference for stocks with large payoffs during earnings announcements.
Keywords: cross-sectional return predictability; extreme returns; earnings announcements; investor attention; lottery-like payoffs